Comparison of Percutaneous Dilatational Tracheostomy with Open Tracheostomy in Intensive Care Unit - Shrestha, Pramesh S; Marhatta, Moda N; Acharya, Subhash P; Shrestha, Ninadini (Journal of Institute of Medicine Nepal, 2019)
Introduction: Tracheostomy is one of the frequent surgical procedure carried out in intensive care unit. Percutaneous tracheostomy is becoming increasingly popular compared to conventional open surgical tracheostomy in ICU. Methods: A prospective randomized trial with twenty patients in each group was conducted to compare the outcomes of percutaneous and surgical tracheostomy. Percutaneous tracheostomy was performed using Ciaglia Blue Rhino technique and surgical tracheostomy was performed using established technique. The outcomes were compared in relation to randomization to tracheostomy, completion of procedure, intra operative and post-operative complications, hospital length of stay and cost. Results: There were no major complications in either group. Most variables studied were not statistically significant. The two groups did not differ in terms of basic demographics or APACHE II score. The only variables to reach statistical significance were time duration from tracheostomy randomization to start of procedure and time taken for completion of procedure. It was mean 31.85±15.35 hours in Percutaneous Tracheostomy group and in Surgical Tracheostomy group it was mean 49.10±23.61 hours respectively (p<0.009). Time taken to perform percutaneous tracheostomy was mean 15.50±3.22 minutes and for surgical tracheostomy it was mean 20.30±3.38 minutes. (p<0.001). Conclusion: Percutaneous dilatational tracheostomy is simple, faster to perform and can be done at bedside to avoid considerable delay in the performance of open tracheostomy where there is high demand for elective and emergency procedures in operating room.